Uso del software libre como parte de equipamiento tecnológico en la escuela de Sistemas de la UTB y su incidencia de compatibilidad con las aplicaciones y herramientas de desarrollo de software informático - Cepeda Ochoa, Elías Isaac (2018)
This research work is oriented to the study of the incidence of compatibility in the existing applications used as computer tools in the School of Systems Engineering of the School of Finance and Computer Science at the Technical University of Babahoyo. How we know free software represents freedom and great benefits for those who use it this is from the economic to the intellectual since it is free it is very easy to access its source code and verify how it was developed, unlike free software that does not necessarily have to be open source to the user or need to be free. It is very important to know that free software is used in companies and high influence companies in the world such as NASA, the NY New York Times, the United States Government use the largest number of applications based on free software this not only it represents important economic savings, but rather on the side of information security is a great point of support. The use of modern tools, resources and software applications allow the development of a learning on a par with technology to overcome obstacles that generally prevent the use and manipulation of free software.